2015
DOI: 10.1186/s12885-015-1773-0
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of sporadic retinoblastoma in relation to maternal health conditions and reproductive factors: a report from the Children’s Oncology group

Abstract: BackgroundThe early age at retinoblastoma occurrence, the most common eye malignancy in childhood, suggests that perinatal factors may contribute to its etiology.MethodsIn a large multicenter study of non-familial retinoblastoma, we conducted structured interviews with the parents of 280 cases and 146 controls to elicit information on health during the perinatal period. We used unconditional logistic regression to assess associations between retinoblastoma and parental fertility treatment, birth control use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
2
20
1
Order By: Relevance
“…No studies to date have published on Wilms’ tumor in relation to pre-pregnancy diabetes. Of the few studies that have specifically reported on gestational diabetes, several have found positive associations [ORs ranging from 2 to 3] with leukemia [18, 20, 21], and others have found no associations with hepatoblastoma and retinoblastoma [23, 24]. We found that several point estimates were elevated for gestational diabetes, but confidence intervals were too wide to draw conclusions from our results.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…No studies to date have published on Wilms’ tumor in relation to pre-pregnancy diabetes. Of the few studies that have specifically reported on gestational diabetes, several have found positive associations [ORs ranging from 2 to 3] with leukemia [18, 20, 21], and others have found no associations with hepatoblastoma and retinoblastoma [23, 24]. We found that several point estimates were elevated for gestational diabetes, but confidence intervals were too wide to draw conclusions from our results.…”
Section: Discussioncontrasting
confidence: 70%
“…The few studies that have assessed the relation between pre-pregnancy BMI and childhood cancer risk have produced conflicting and inconclusive results [6, 15, 16, 2326]. Given the unexpected pattern of a greater risk of these cancers with overweight but a drop in risk with obesity, it is notable that two studies of leukemia and retinoblastoma also observed an attenuation of the size of the estimate in the obese group [24, 26]. This may be explained by an increased risk of competing outcomes that cause selective survival of affected fetuses specifically fetal death, stillbirth, and neonatal, perinatal, and infant deaths that have been consistently observed to be associated with higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Moderate Greenop, 2015, Australia [ 64 ] 2003–2006;2005–2010 PC-CS 592/1389 0–14 Aus-ALL and Aus-CBT Population ALL ( N = 314); brain tumors ( N = 278) Never/< 3/3- < 6/≥ 6; Ever vs. never Questionnaire to mothers Matched: age, sex, and state of residence.Adjusted: Matched variables, maternal education, maternal age at birth, birth order, proportion of optimum birth weight. 7 Moderate Heck, 2015, USA and Canada [ 65 ] 2006–2011 HC-CS 243/134 0–15 Wills Eye Hospital in Philadelphia, or the Children’s Oncology Group Friends or unrelated children of case family Retinoblastoma ( N = 243) < 1/1–6/7–11/≥ 12; Ever vs. never Telephone interview of parents Matched: age.Adjusted: child’s age at interview, mother’s race/ethnicity, mother’s educational attainment, and household income. 7 Moderate Amitay, 2016, Israeli [ 66 ] 2005–2013 PC-CS 178/357 1–18 The hematologic departments of five large Israeli hospitals Population Leukemia ( N = 117); lymphoma ( N = 61) ≤ 6 vs. > 6 Interview of mothers Matched: age, gender, and spoken language.Adjusted: none.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining cases are considered sporadic; these children can have bilateral or unilateral diesease 1 . In sporadic bilateral retinoblastoma, a de novo germline alteration in RB1 occurs in the egg or sperm cell prior to conception and the second alteration occurs somatically after conception 2‐4 . In sporadic unilateral retinoblastoma, both alterations in RB1 occur after conception in somatic cells of the developing retina, although up to 15% can be caused by germline alterations 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In sporadic bilateral retinoblastoma, a de novo germline alteration in RB1 occurs in the egg or sperm cell prior to conception and the second alteration occurs somatically after conception 2‐4 . In sporadic unilateral retinoblastoma, both alterations in RB1 occur after conception in somatic cells of the developing retina, although up to 15% can be caused by germline alterations 3,4 . Prior studies have shown an estimated 85% of de novo germline alterations in sporadic bilateral retinoblastoma are of paternal origin 5 .…”
Section: Introductionmentioning
confidence: 99%